The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1039/d0fo02252g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fibre and protein content on intestinal fibre degradation, short-chain fatty acid and microbiota composition in a high-fat fructose-rich diet induced obese Göttingen Minipig model

Abstract: Obesity-related metabolic syndrome has been linked with gut microbiome dysbiosis while dietary fibre (DF) and protein can modify the gut microbial ecosystem and metabolism. After 20-weeks’ on a high-fat fructose-rich...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 63 publications
0
18
0
1
Order By: Relevance
“…However, fermentation efficiency also depends on the structural composition of the dietary fibre. Xu et al (2020) also found similar results in pigs with ad libitum access to feed with a high dietary fibre content containing whole wheat grain and wheat bran [ 94 ]. In this study, arabinoxylan (AX) was degraded through the GIT up until the mid-colon.…”
Section: Impact Of Meal Size and Frequency On Transit Time And Digestibility Of Nutrientsmentioning
confidence: 78%
See 2 more Smart Citations
“…However, fermentation efficiency also depends on the structural composition of the dietary fibre. Xu et al (2020) also found similar results in pigs with ad libitum access to feed with a high dietary fibre content containing whole wheat grain and wheat bran [ 94 ]. In this study, arabinoxylan (AX) was degraded through the GIT up until the mid-colon.…”
Section: Impact Of Meal Size and Frequency On Transit Time And Digestibility Of Nutrientsmentioning
confidence: 78%
“…In this study, arabinoxylan (AX) was degraded through the GIT up until the mid-colon. Butyrate production was increased modestly by the high consumption of fibre in the diet [94]. A study by Glitsø et al (1999) looked at the degradation of AX in different rye diets with pigs being fed a restricted amount of feed twice a day [95].…”
Section: Impact Of Meal Size and Frequency On Transit Time And Digestibility Of Nutrientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the SCFA levels, the results showed that acetate, propionate, butyrate, and isobutyrate were detectable at the μM level in the small intestine of mice in all treatments, which was lower than in the cecum and the colon (mM level) reported in a previous study. 2,34 The results could be attributed to the short span-life/short transition time of microbiota under the harsh and less stable environment in the small intestine. 35 Notably, the present work further showed that acetate and propionate concentrations were relative high, even up to mM level, compared with other SCFAs in the STS treatment (Figure 6A,B).…”
Section: ■ Discussionmentioning
confidence: 99%
“…butyricum 处理 A c c e p t e d https://engine.scichina.com/doi/10.1360/SSV-2021-0363 可有效降低非酒精性脂肪肝的发生率 [40,45,46] ,表明 C. butyricum 具有调控肝脏脂质代谢的能力。 Akkermansia muciniphila (A. muciniphila)是一种存在于肠道黏液层的粘蛋白降解菌,该菌在 改善宿主代谢功能及免疫应答方面有重要作用 [23] 。上述移植瘦肉型长白猪粪菌受体小鼠其肠道 Akkermansia 丰度显著高于脂肪沉积型金华猪受体小鼠 [21] ,提示 Akkermansia 和宿主脂质代谢相 关。大量以小鼠为模型的研究表明该菌干预可逆转高脂饮食诱导的代谢紊乱,主要表现在抑制脂 肪组织的沉积与炎症发生、 改善机体内毒素血症、 胰岛素抵抗和提高肝脏胆汁酸代谢等 [24-26] [47] 。 经巴氏灭活后的 A. muciniphila 会失去调控脂质代谢及黏液层厚度的能力 [27] ,但另一项研究则表 明小鼠灌喂经巴氏灭活的 A. muciniphila 仍可有效增加全身能量消耗,促进白色脂肪褐变,并加 速粪便能量排出 [48] 。最近的一项研究表明,A. muciniphila 是通过重塑宿主肠道微生物结构介导 肝脏 L-天冬氨酸水平升高以改善代谢功能紊乱相关脂肪肝疾病(metabolic dysfunction-associated fatty liver disease, MAFLD)。体外肝细胞试验验证了 L-天冬氨酸可抑制脂质积累,证实了 A. muciniphila 是通过调控 L-天冬氨酸代谢以改善机体脂质代谢 [47] 。 也有研究者表明, A. muciniphila 是通过促进肠道内源性大麻素的水平控制机体炎症的发生、 改善肠道屏障并促进肠道小分子肽类 物质的分泌从而控制代谢综合征的发生 [27] 。目前关于该菌在猪脂质代谢调控上的基础研究存在 缺口,后续可通过开展相关试验验证该菌在调控猪脂质代谢方面的功能。 3 猪肠道微生物代谢产物调控脂质代谢作用与机制 3.1 短链脂肪酸 肠道微生物的一个重要生理功能是可以代谢宿主酶系统不能完全水解的膳食纤维 [49] 。后肠 微生物可将难以消化的膳食纤维和抗性淀粉发酵生成 SCFAs,主要为乙酸、丙酸和丁酸 [50] 。这 些小分子代谢物在调控宿主能量代谢中起重要作用, 是机体用于脂肪酸及葡萄糖从头合成的原料 [51] 。目前研究认为 SCFAs 可作为信号分子激活细胞膜表面 G 蛋白偶联受体 43(G-protein-coupled receptor, GPR43), 通过调控靶器官胰岛素敏感性、 宿主食欲及增加能量代谢, 进而调节脂质积累, 维持机体代谢稳态 [50,52] 。对高脂高糖诱导的肥胖猪进行高纤日粮干预,结果显示纤维干预下肠 道内富集了大量产丁酸的细菌,如 Blautia,Faecalibacterium 和 Peptococcus。这些细菌诱导肠道 丁酸含量略微上升,同时肠腔内丁酸以丁酸盐的形式存在于静脉血中 [53] 。为探究机体脂质代谢 对丁酸的响应能力,研究者通过静脉注射给育肥猪输入丁酸钠,结果显示该物质可加速脂肪动员 并抑制硬脂酸的合成 [54] 。另一研究通过盲肠瘘管给育肥猪灌注丙酸钠,该物质显著降低了血清 及肝脏甘油三酯的水平并促进肽 YY (peptide YY,PYY)的分泌,从而影响机体脂肪代谢 [55] 。上 述结果表明 SCFAs 可被肠细胞吸收进入机体循环中发挥作用,其主要通过激活 GPR43 受体,进 而抑制脂肪细胞中的胰岛素信号,同时加速宿主肌肉组织和肝脏对能量的消耗 [52] ,达到抑制脂 肪组织肥大的效果。宿主中大部分 SCFAs 由肠道微生物产生,但 SCFAs 是否可以独立于肠道微 生物发挥功能尚未可知。有研究者通过给无菌猪灌喂 SCFAs 混合物(乙酸、丙酸、丁酸),结果显 示 SCFAs 可上调无菌猪背最长肌肉毒碱棕榈酰转移酶(Carnitine palmitoyl transferase 1,CPT-1)的 表达量;与对照组相比,SCFAs 处理组肝脏脂肪合成相关基因表达量下调,AMPK 磷酸化信号 被激活 [56] , 表明宿主脂质氧化加速, 外源 SCFAs 可不依赖肠道微生物发挥作用。 由此可见, SCFAs [57] ,这些物质主要参与神经递质的传递,提供 DNA 表观调控的甲基供体,参与细胞信号传导以及机体能量代谢 [57][58][59][60][61][62] 。日粮中适当添加胆碱可显著改 善宫内受限仔猪(intrauterine growth retardation, IUGR)的脂质代谢情况, 主要表现在肌肉中脂肪酸 合成酶(fatty acid synthetase, FAS)及固醇调节元件结合蛋白 1 (sterol regulatory element-binding proteins 1, SREBP1)基因表达量上调,同时脂肪氧化分解相关基因表达量...…”
Section: 两者除了在菌群组成上有相似性,其菌群功能也高度相似。这一点可通过对比分析人类与猪肠道 微生物组基因信息进行验证,分析结果...unclassified